(untitled) (INNOVATIVE ECONOMY, 2020)
Hrabchak V.I. INNOVATIVE ASPECTS OF MANAGEMENT CONCEPT BY THE REPUTATION OF TRADE ENTERPRISES Purpose. The aim of the article is to determine the peculiarities of the management process by the reputation of trade enterprises and to establish its interconnection with innovation development. Conceptual provisions substantiation relevant, as well as the recommendations creation of improving the reputation management role in a rapid technological change context. Methodology of research. The following methods are used in the research process: methodology included provisions application of the theory and practice of innovation development and the theory of organization as methodological principles; developed and substantiated conceptual approaches are also used. Methods of analogy and goals structuring, generalization are used to identify the features of managing the enterprise reputation and developing proposals for the formation of a reputation management system for a trading company as a component of development innovation. Findings. The results of research presents the developed enterprise innovative development management interconnection conceptual model with the formation process and reputation providing taking into account a modern management and innovation principles. It is substantiated that reputation, unlike the image, should be considered as more economical than social category, as it significantly influences the attractiveness of the company for investors, increases its capitalization, allows to increase the income, provides stronger positions on the way of new markets. The peculiarities and role of online reputation management as an effective management technology through which the formation of the company positive image in business takes place are revealed in the article. Practical experience shows that the goods and services choosing process, modern consumers (clients) are increasingly resorting not to the advice of relatives, but to various reviews on Internet resources. Originality. The research scientific novelty is to determine and substantiate the conceptual foundations and to deepen the scientific, theoretical and practical provisions for the trading enterprises reputation managing process formation, considering the principles of their application in the context of innovative development issues actualization. Practical value. The use of the developed provisions in practice will help the leadership of enterprises to effectively organize the reputation management process with strictly defined principles and algorithms, and will allow the investors, customers, suppliers and qualified stuff to be interested and retained; to maintain the financial stability, and a hence to be more competitive. Key words: trade enterprise; innovative development; reputation; reputation management; conceptual approach.